1ª Lei da Termodinâmica a partir do conceito de entropia - SOUSA, Anna Karollyni Lopes (Universidade Federal do Tocantins, 2023)
For most people, it is impossible not to encounter, in daily life, applications of thermodynamics. In addition to being a content that we study in schools, we are surrounded by thermal phenomena, through devices and applications of the laws of thermodynamics. The initial objective is to carry out a historical survey addressing the experiments that led to the formulation of the first law of thermodynamics. The second objective is to deduce the 1st law of thermodynamics from the concept of entropy. We do not normally treat the first law of thermodynamics in this way, but it is relevant to note how the laws of thermodynamics are interdependent. To carry out the work, the methodology of exploratory bibliographic research and the deductive method were used. The 1st law remains valid from the perspective adopted